Effects of Pilates Exercises on the Social Physical Concern of Patients with Fibromyalgia Syndrome: A Pilot Study - Nimet Korkmaz, (Archives of Rheumatology, 2010)
Objective: The goal of this study was to investigate the effect of Pilates exercises on the social physical concern (SPC) of patients with fibromyalgia syndrome (FMS). We also aimed to determine the effect of Pilates exercises on strength, body mass index (BMI), pain, and depression. Materials and Methods: Twenty-five female patients with an age range of 33 to 63 years (mean: 49.16±7.51) were evaluated. All patients had been diagnosed with FMS according to the American College of Rheumatology (ACR) criteria. Patients underwent a Pilates exercise program consisting of one hour of exercise performed three times per week for 12 weeks. Prior to exercise and at the end of the 12th week, the patient's weight, grip strength of the hands, back strength, body fat ratio, and BMI were measured. Before- and after-exercise measurements were compared. The patient pain level was determined using the visual analog scale (VAS). Beck Depression Inventory (BDI) was used to define the depression level of patients. SPC level of patients was obtained by Social Physique Anxiety Scale (SPAS). The correlations between SPC scores and anthropometric values and pain and depression levels were evaluated. Results: Pilates exercises significantly improved the weight, BMI, body fat ratio and SPC and pain level of the patients. No statistically significant change was found for grip strength of either hand or back strength. A statistically significant correlation was found between SPC scores and the body fat ratio, weight, BMI, and pain and depression scores of patients before and after the exercise program. Conclusion: A 12-week Pilates program had positive effects on anthropometric parameters, SPC, and pain and depression levels of FMS patients. Patients with FMS can safely perform Pilates exercises to control weight, improve physical appearance, and reduce SPC and pain and depression levels, and no adverse side effects were observed. To obtain further evidence regarding the effectiveness of Pilates exercises, additional studies involving different patient groups are required.(Turk J Rheumatol 2010; 25: 201-7)